FAKTOR PENGHAMBAT PENERAPAN SISTEM PROFIL DESA DAN KELURAHAN (PRODESKEL) DI KECAMATAN GIRI - Nur Syaida; Leni Vitasari; Niko Pahlevi Hentika (Jawa Dwipa, 2025)
This study investigates the inhibiting factors in the implementation of the Village and Sub-District Profile System (Prodeskel) in Giri Subdistrict, Banyuwangi Regency. Using a descriptive qualitative approach, data were collected through interviews, observations, and document analysis. The analysis refers to the six dimensions of policy implementation barriers proposed by Warwick (1979), namely: magnitude of change, number of actors involved, number of decision points, alternative commitments or preferences, intrinsic complexity, and timing. Findings indicate that three of these dimensions significantly hinder the process. First, overlapping responsibilities especially in urban administrative units cause operators to deprioritize Prodeskel tasks (alternative commitments). Second, technical challenges such as slow system performance and login issues (intrinsic complexity) reduce efficiency and data accuracy. Third, a limited time frame particularly for sub-districts, which only receive about one month for data entry constrains the overall implementation (timing). On the other hand, the other three dimensions organizational change, actor involvement, and decision-making structures were not identified as barriers, as coordination across stakeholders was smooth and decisions were made in a direct, administrative manner. This study suggests the importance of optimizing time management, enhancing technical infrastructure, and distributing tasks more equitably to ensure accurate and consistent data reporting at the local government level.